2010
DOI: 10.1007/s10577-010-9118-y
|View full text |Cite
|
Sign up to set email alerts
|

The winged-helix transcription factor JUMU regulates development, nucleolus morphology and function, and chromatin organization of Drosophila melanogaster

Abstract: The PEV-modifying winged-helix/forkhead domain transcription factor JUMU of Drosophila is an essential protein of pleiotropic function. The correct gene dose of jumu is required for nucleolar integrity and correct nucleolus function. Overexpression of jumu results in bloating of euchromatic chromosome arms, displacement of the JUMU protein from the chromocenter and the nucleolus, fragile weak points, and disrupted chromocenter of polytene chromosomes. Overexpression of the acidic C terminus of JUMU alone cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Moreover, localization studies for Delta (Dl) and Ecdysone Receptor (EcR) show a precise colocalization of EGFP and the protein specific antibodies for Delta and EcR, respectively ( Figure 2—figure supplement 1 ). Finally, proteins localize to the proper subcellular compartments as shown in Figure 2B for a cytoplasmic or organelle present in cytoplasm associated ( Catalase ), nuclear ( H6-like-homeobox : Hmx ) and membrane associated protein ( dpr15 ) ( Figure 2B ) ( Beard and Holtzman, 1987 ; Hofmann et al, 2010 ; Özkan et al, 2013 ). These examples indicate that the EGFP patterns faithfully report expression and protein distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, localization studies for Delta (Dl) and Ecdysone Receptor (EcR) show a precise colocalization of EGFP and the protein specific antibodies for Delta and EcR, respectively ( Figure 2—figure supplement 1 ). Finally, proteins localize to the proper subcellular compartments as shown in Figure 2B for a cytoplasmic or organelle present in cytoplasm associated ( Catalase ), nuclear ( H6-like-homeobox : Hmx ) and membrane associated protein ( dpr15 ) ( Figure 2B ) ( Beard and Holtzman, 1987 ; Hofmann et al, 2010 ; Özkan et al, 2013 ). These examples indicate that the EGFP patterns faithfully report expression and protein distribution.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that Jumu regulates nucleolar morphology and function and chromatin organization and that the correct genetic dose is required for nucleolar integrity and correct nucleolar function (Hofmann et al, 2010). Here, we found that Jumu also regulates the hemocyte differentiation of the lymph gland in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in these genes lead to haplo-insufficient phenotypes of delayed development, shortened and thin bristles, and reduced viability and fertility. Other Drosophila genes known to encode nucleolar processing and/or assembly factors have also been characterized in terms of their mutant phenotype; those that have been better characterized include minifly , 197 modulo , 198 - 200 viriato , 201 dribble , 202 jumeaux , 203 pitchoune , 204 and Nopp140 205 , 206 . The minifly gene (also called Nop60B ) encodes a pseudouridylase homologous to human DCK1 .…”
Section: Endogenous Mutations: the Ribosomopathiesmentioning
confidence: 99%